EVALUASI KAPASITAS PRODUKSI DAN IDENTIFIKASI KEBUTUHAN PENGEMBANGAN MESIN LEMANG BERBASIS VOICE OF CUSTOMER - Anggraini Dwi Saputri; Anita Susilawati; Awaludin Martin; Feblil Huda; Dinni Agustina; Yogie Rinaldy Ginting; Herisiswanto Herisiswanto; Annisa Wulan Sari; Dedy Masnur; Putri Nawang Sari; Ari Andriyas Puji; Dodi Sofyan Arief; Yohanes Yohanes (Jurnal Pengabdian Kompetitif, 2026)
The implementation of the Closed Rotary Lemang Baking Machine at Rumah Lemang MSME in Pekanbaru improved burning time efficiency by 50%–62.5% per batch. However, field evaluation revealed a critical capacity gap: machine capacity (10 bamboo/batch) was significantly lower than traditional production capacity (40 bamboo/batch), resulting in lower actual throughput (6–7 bamboo/hour vs. 10–13 bamboo/hour) and reduced daily output (20–30 vs. 40 bamboo). This study analyzed this gap through throughput analysis and identified second-generation machine requirements using Voice of Customer (VoC). Methods included in-depth interviews with the MSME owner, production performance measurement, and comparative gap analysis. VoC results identified an ideal capacity of 50 bamboo/batch, with the owner already planning an independent modification as an indication of active technology adoption. This study recommends an iterative development approach with modular second-generation machine specifications grounded in real user needs.